2002
DOI: 10.1182/blood.v99.6.1885
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid cell factor–1 is a critical survival factor for multiple myeloma

Abstract: IntroductionMultiple myeloma (MM) is a B-cell malignancy characterized by the accumulation of plasma cells with a low proliferation index and an extended life span. 1,2 Despite improvements in event-free and long-term survival resulting from autologous stem cell transplantation, MM remains an incurable disease in the majority of patients. 3,4 In the initial phases of this disease, the malignant plasma cells are dependent on the supportive environment of the bone marrow, which is at least partly responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
274
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(288 citation statements)
references
References 76 publications
11
274
1
2
Order By: Relevance
“…Mcl-1, which is highly expressed in hematopoietic cells, is an antiapoptotic member of the Bcl-2 family (Craig, 2002). In multiple myeloma (MM) cells, in which IL-6 plays a critical role in proliferation and survival, upregulation of Mcl-1 was shown to mediate the antiapoptotic effect of IL-6 (Jourdan et al, 2003), whereas the downregulation of the gene by antisense technology led to apoptosis (Derenne et al, 2002;Zhang et al, 2002;Le Gouill et al, 2004). In a study conducted on 12 IL-6-dependent human myeloma cell lines, Mcl-1 was found to be the only Bcl-2 family member (out of ten considered in the study) overexpressed in all the cell lines and regulated by IL-6, thus suggesting Mcl-1 as a major mediator of the survival activity of the cytokine (Craig, 2002;Jourdan et al, 2003;Le Gouill et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Mcl-1, which is highly expressed in hematopoietic cells, is an antiapoptotic member of the Bcl-2 family (Craig, 2002). In multiple myeloma (MM) cells, in which IL-6 plays a critical role in proliferation and survival, upregulation of Mcl-1 was shown to mediate the antiapoptotic effect of IL-6 (Jourdan et al, 2003), whereas the downregulation of the gene by antisense technology led to apoptosis (Derenne et al, 2002;Zhang et al, 2002;Le Gouill et al, 2004). In a study conducted on 12 IL-6-dependent human myeloma cell lines, Mcl-1 was found to be the only Bcl-2 family member (out of ten considered in the study) overexpressed in all the cell lines and regulated by IL-6, thus suggesting Mcl-1 as a major mediator of the survival activity of the cytokine (Craig, 2002;Jourdan et al, 2003;Le Gouill et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Therefore, we sought to induce dual inhibition of Mcl-1 by combining a proteasome inhibitor, carfilzomib, with a multikinase inhibitor, TG02. Individually these drugs could induce apoptosis in multiple myeloma cell lines, but in combination they had at least additive effects.…”
Section: Discussionmentioning
confidence: 99%
“…16 In order for MM cells to resist apoptosis they are dependent on the anti-apoptotic protein Mcl-1 for survival. [17][18][19] Mcl-1 is an oncogene that promotes tumorigenesis by binding to pro-apoptotic proteins Bak and Bim, thus preventing the release of cytochrome c from the mitochondria and subsequent caspase activation. 20 Given that most MM cells are dependent on Mcl-1 for survival it would be beneficial to inhibit Mcl-1 to increase the apoptotic response in these cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential for the survival of plasma cells in vitro (Zhang et al, 2002), and overexpressed by those from patients with relapse or poor prognosis (Wuillelme-Toumi et al, 2005).…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%